2016
DOI: 10.1038/srep21225
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of doxorubicin and curcumin by pH-sensitive prodrug nanoparticle for combination therapy of cancer

Abstract: Ample attention has focused on cancer drug delivery via prodrug nanoparticles due to their high drug loading property and comparatively lower side effects. In this study, we designed a PEG-DOX-Cur prodrug nanoparticle for simultaneous delivery of doxorubicin (DOX) and curcumin (Cur) as a combination therapy to treat cancer. DOX was conjugated to PEG by Schiff’s base reaction. The obtained prodrug conjugate could self-assemble in water at pH 7.4 into nanoparticles (PEG-DOX NPs) and encapsulate Cur into the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 46 publications
5
133
1
3
Order By: Relevance
“…The nanoformulation of curcumin is versatile. Free curcumin, polymeric, liposomal and other types of formulations of curcumin can be co/concurrently-delivered with chemotherapy, such as camptothecin (CPT) [86], etoposide [45, 87], platinum [88], PTX [48, 89] and DOX [90, 91] to induce synergy. One study utilized flaxseed oil nanoemulsion to effectively encapsulate PTX and curcumin to enhance the cytotoxicity against both wild-type and resistant ovarian tumor cell line SKOV3[48].…”
Section: Rationales and Significance Of Traditional Combination Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoformulation of curcumin is versatile. Free curcumin, polymeric, liposomal and other types of formulations of curcumin can be co/concurrently-delivered with chemotherapy, such as camptothecin (CPT) [86], etoposide [45, 87], platinum [88], PTX [48, 89] and DOX [90, 91] to induce synergy. One study utilized flaxseed oil nanoemulsion to effectively encapsulate PTX and curcumin to enhance the cytotoxicity against both wild-type and resistant ovarian tumor cell line SKOV3[48].…”
Section: Rationales and Significance Of Traditional Combination Thmentioning
confidence: 99%
“…Single or multiple drug-conjugated polymers exhibiting amphiphilic properties were also used to encapsulate small-molecule drugs for combination therapy based on the supramolecular interaction between drug-conjugated polymer carriers and the other drugs [90, 107110]. For example, the platinum (IV) prodrug is conjugated to a PLA backbone via an ester bond to form the PLA-Pt(IV) conjugate [108, 109].…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
“…13 Zhang et al reported that co-delivery NPs of DOX and curcumin could simultaneously release the drugs in the acidic microenvironment of cancer cells. 23 However, even if these drugs are transported to the cytoplasm, they still face the difficulty of escaping the fate of efflux associated with P-gp. Therefore, the intracellular precision release of NDDS-loaded P-gp substrates is still a demanding issue.…”
Section: Introductionmentioning
confidence: 99%
“…When an intracellular pH-triggered drug release carrier is incorporated with a tumour-targeting ligand, this multifunctional nanocarrier can recognize tumour cells and release the encapsulated drug at tumour sites in a controlled manner12. A variety of nanomaterials responding to pH stimuli, such as liposomes, micelles, polymeric and prodrug nanoparticles, have been synthesised and developed as effective drug delivery systems3456. However, not much effort has gone toward developing a pH-responsive drug delivery system based on virus-like nanoparticles (VLNPs).…”
mentioning
confidence: 99%